The Influence of Problem Based Learning Assisted by PhET on Students’ Critical Thinking Skills on the Material of the Earth and Solar System - Parhusip, Jeremia Obrial Steven; Simamora, Pintor (UNIVERSITAS NEGERI MEDAN, 2025)
This research investigates the impact of using the Problem-Based Learning (PBL) model supported by PhET simulation media on students’ critical thinking skills, specifically in enhancing each indicator of critical thinking on the Earth and Solar System topic for Grade VII students at SMP Negeri 13 Medan during the 2024/2025 school year. Based on observations made, it is known that students have not been thinking critically, as indicated by their inability to interpret tables or images, analyze problems, and explain issues. The study adopts a quasi-experimental approach with a pretest-posttest control group design. The participants included two classes: class VII-2 as the experimental group receiving PBL with PhET, and class VII-6 as the control group receiving conventional instruction. Cluster random sampling was employed to determine the sample. Data were gathered through tests and observational methods, and analyzed using the Independent Sample t-test for hypothesis testing. The experimental group had an average pretest score of 12.9 and a posttest score of 77.7, while the control group scored 15.7 and 65.6, respectively. The results confirmed a significant influence of the PBL approach, aided by PhET media, on students’ critical thinking development. Furthermore, the N-gain analysis revealed that the experimental class showed a higher average percentage gain across all indicators compared to the control class.